Multi-dimensional visualization of sustainable filtration. (July 2016) - Howarth, J; Anand, S
The paper determines that the cause of retardation of innovation for industrial filtration applications is commercial supposition rather than technical performance. The paper describes a multi-dimensional framework for characterizing the required filtration attributes for attaining a more sustainable filter for bespoke industrial applications. This framework appreciates the fact that bespoke applications have complex environments as such a subjective approach is taken and the results are indexed to that used commercially in the application. Paint exhaust filtration has been used as the papers' framework example and laboratory characterization of this bespoke filtration is undertaken revealing the multiple key areas of focus. This multi-dimensional approach demonstrates it is possible to utilize subjective visual characterization followed by quantitative methods as an effective facilitator of sustainable filtration re-engineering.